PEMENUHAN HAK PARTISIPASI ANAK MELALUI FORUM ANAK DAERAH KABUPATEN BANDUNG DALAM PELAKSANAAN “PROGRAM KABUPATEN BANDUNG LAYAK ANAK” - Andika Subagja, Aria; Anwar, Alii; Gunawan, Uga Pratama (Politeknik Kesejahteraan Sosial Bandung, 2024)
Recently, decision-making regarding children's right to participate has become a major focus in development policies and programs in various regions of Indonesia. One significant initiative in this regard is the